PENERAPAN MEDIA PEMBELAJARAN LECTORA INSPIRE UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR PERHITUNGAN KONSTRUKSI MESIN SISWA KELAS XI MESIN DI SMK PIRI SLEMAN - Sandi Sanjaya; Suparmin Suparmin (Universitas Sarjanawiyata Tamansiswa, 2017)
The objection of this study is to increase the level of interest and learning achievement about calculation of construction machinery subjects in the 11th grade of mechanical class of PIRI Sleman Vocational High School through the Lectora Inspire learning media. The type of this research is classroom action research. This research was conducted in two cycles. The research subject is mechanical class of PIRI Sleman Vocational High School, which includes fifteen male students. The data collection method is using the evaluation data which is collected through the learning achievement test, Beside that, the research is used to know the students interest in learning subjects Construction Engineering Calculations using a questionnaire. Data analysis method used is a comparative technique that compares the results of pre-test and post-test. The result showed that by using the Lectora Inspire learning media, the level of interests and learning achievement about calculation of construction machinery subjects in the 11th grade of mechanical class of PIRI Sleman Vocational High School was increased. In the first cycle, students interest reached about 64.87%, which is included in the high criteria. The initial competency of the subject obtained from the pre-test showing that there are three or 20% students have fulfilled the minimum achievement criteria, while twelve students or 80% students haven’t fulfilled it yet. The enhancement of student achievement in the first cycle, who passed the minimum achievement criteria is ten students with a percentage of 66.67% or the mean value is 75.07. For the second cycle of post test result showed the students who reached 75 point is thirteen students with a percentage of 86.67% or the mean value is 75.07. Overall, the interest level for study calculations of construction machinery in mechanical class of PIRI Sleman Vocational High School increased by 66.67%.